Crônicas de Graciliano Ramos em Cultura política (1941- 1944): estudo crítico - Faria, Patricia Aparecida Gonçalves de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The alagoano writer Graciliano Ramos (1892-1953) has always been known and honored by the criticism and the public as a great writer of novels and memoirs. After being politically arrested during the time of the Estado Novo, he decided, after leaving th prison and achieving recognition among the publishers and known intellectuals, to live in Rio de Janeiro. However, he faced up serious financial problems in the capital, along with his wife and kids, and he noticed that living only of literature wouldn’t be so easy. Joining the practice of writing novels and short stories the to the press of the time, he collaborated from the years of 1941 to 1944 in Cultura Política: revista mensal de estudos brasileiros – monthly magazine of Brazilian studies - (1941-1944), the main publication of the Press and Advertising Department (PAD), controlled by the Estado Novo, which was responsible to send him to prision in 1936, without, at least, a formal accusation. Thus, considering the intellectual and literary path of the writer of Vidas Secas, this research aims, from the analysis of some chronicles published in Cultura Política and later chosen to be part of the posthumous publication of Viventes das Alagoas (1962) and Linhas Tortas (1962), at studying the characteristics of the magazine and its strategies to maintain the group of important people, such as Graciliano Ramos and, certainly, to verify the strategies of the writing used by the writer to help the State without, however, to surrender to the government ideology. This study still aims at defining in the chronicles of Cultura Política the relation to the writer’s point of view with the Brazilian northeast custom, the importance of the language and the literary life and the political and economical connection linked, more specifically, to the northeast

O escritor alagoano Graciliano Ramos (1892-1953) sempre foi reconhecido e aclamado pela crítica e pelo público como grande escritor de romances e memórias. Preso político durante o período do Estado Novo, após deixar o cárcere e alcançar o reconhecimento de editores e intelectuais renomados, decidiu fixar residência no Rio de Janeiro. Contudo, enfrentou sérias dificuldades financeiras na capital, juntamente com esposa e filhos, e constatou que sobreviver somente de literatura não era uma tarefa fácil. Aliando a prática da escrita de romances e contos com a imprensa da época, colaborou durante os anos de 1941 a 1944, com Cultura Política: revista mensal de estudos brasileiros (1941-1944), principal publicação do Departamento de Imprensa e Propaganda (DIP), controlado pelo Estado Novo, responsável pela sua prisão em 1936, sem a mínima acusação formal. Assim, considerando o percurso intelectual e literário do autor de Vidas Secas, este trabalho pretende, a partir da análise das crônicas publicadas, na fonte primária Cultura Política, e posteriormente selecionadas para compor as publicações póstumas de Viventes das Alagoas (1962) e Linhas Tortas (1962), levantar as características da revista e suas estratégias para manter em seu rol de colaboradores figuras importantes, como Graciliano Ramos e, certamente, verificar as estratégias de escrita utilizadas pelo escritor para servir o Estado sem, contudo, se render a ideologia do governo. O presente estudo pretende, ainda, observar nas crônicas de Cultura Política a ótica do escritor ao discutir os usos e costumes nordestinos, a importância da linguagem e da vida literária, as relações políticas e econômicas ligadas, mais estritamente, ao nordeste
Keywords: Ramos, Graciliano 1892-1953; Periódicos brasileiros; Cronicas brasileiras; Literatura brasileira; Literature